Selected extended papers of the 12th International Conference on Practical Applications of Computational Biology and Bioinformatics (PACBB) - Florentino, Fdez-Riverola (2019)
This special issue includes extended versions of a number of papers selected from the International Conference on Practical Applications of Computational Biology and Bioinformatics (PACBB 2018) that was held in Toledo (Spain) in June 2018. This forum, already in its twelfth edition, aims to reunite and promote the collaboration among researchers developing applied Bioinformatics or Chemoinformatics research.